Foreign Body Reaction Mimicking Sarcoma. Issue 12 (December 2017) - Segreto, Francesco; Marangi, Giovanni Francesco; Delle Femmine, Pietro Francesco; Greco, Federico; Persichetti, Paolo
Abstract : Foreign body reaction can sometimes mimic the features of sarcoma. A 42-year-old patient was referred to our department for a rapidly growing subcutaneous mass in the posteromedial aspect of the lower leg. Ultrasonography and magnetic resonance imaging were highly suggestive for soft tissue sarcoma. The patient underwent surgical resection. The histho-pathologic diagnosis found that the supposed sarcoma was an inflammatory pseudo-tumor, also referred to as "gossypiboms". Surgeons must be aware that, in some cases, the imaging cannot reliably distinguish between sarcoma and foreign body reaction.